The Influence of Work Ethic, Work Discipline, and Communication on Employee Performance at the Yogyakarta Special Region Tourism Office - Swastika, I Gede; Kirana, Kusuma Chandra; Septyarini, Epsilandri (Electronic Journal of Education, Social Economics and Technology, 2025)
This study examines the influence of work ethic, work discipline, and communication on employee performance at the Yogyakarta Special Region Tourism Office. A quantitative research approach was employed, utilizing a structured questionnaire distributed to all 74 employees through a census sampling method. Data were analyzed using SPSS version 25, incorporating statistical tests such as normality, multicollinearity, heteroskedasticity, t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that work discipline and communication have a significant positive impact on employee performance, while work ethic does not exhibit a direct effect. Strong work discipline fosters accountability and productivity, whereas effective communication enhances collaboration and efficiency. These results underscore the necessity for organizations to reinforce discipline and communication strategies to optimize employee performance. The study contributes to the understanding of workplace dynamics by emphasizing key determinants of productivity. Future research should explore additional factors influencing employee performance, particularly in the context of technological advancements and evolving work environments.